Fecundity and Gonadal Maturity of Gongota Loach Somileptes Gongota (Hamilton) (Cobitidae) in the Habitat of the Someswari River - Saha, BK; Saha, A (Bangladesh Journal of Scientific and Industrial Research, 2012)
Fecundity and gonadal maturity of gongota loach, Somileptes gongota (=Cobitis gongota) (Ham.) were studied from October 2005 to September 2006. The fecundity of S. gongota varied from 1540 to 91500. The average fecundity was calculated as 34916.85 ± 25967.51. The maximum and minimum fecundities were determined as 72520± 13423.59 and 2891.44 ± 1084.19 in June and March, respectively. The relationships between fecundity and other variables were calculated and found to be straight, linear and positively significant. The gonadal maturity of S.gongota was determined by using five methods viz. Percentage of gravid females against time, Gonado- Somatic Index (GSI), Gonadal-length Index (GLI), Ova Diameter (OD) and Colour of Ovary (CO). The highest percentages of gravid females were recorded as 100 in June and July. The overall percentage of gravid females was determined as 58.15±30.11. The Gonado-Somatic Index level was recorded as 7.76 8.66 with maximum (26.17±3.13) in May. The Gonadal-Length Index level was determined as 35.34 ±10.40 having the highest (50.31± 3.04) in May. The Ova Diameter ranged from 0.1-1.5 mm with a mean value of 0.53± 0.3 mm. The highest ova diameter was found to be 1.40±0.23 mm in June. The colour of ovary was recorded as reddish orange and orange in the months of May to June and July, respectively. Key words: Fecundity; Gonadal maturity Ova diameter DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9609 BJSIR 2011; 46(4): 573-78